2021
DOI: 10.1016/j.jadohealth.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Sexual and Reproductive Health Care: Findings From Primary Care Providers Who Serve Adolescents

Abstract: Among U.S. primary care physicians who delivered sexual and reproductive health (SRH) services to adolescents before the COVID-19 pandemic, we examine (1) changes in availability of in-person SRH services; (2) changes in accessibility and utilization of SRH services; and (3) use of strategies to support provision of SRH services during the pandemic. Methods: Data were from the DocStyles provider survey administered SeptembereOctober 2020. Descriptive analyses were restricted to family practitioners, internists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 34 publications
4
45
0
2
Order By: Relevance
“…In the US, one-quarter of physicians surveyed who provided telehealth for SRH issues reported confidentiality concerns. 15 Others have also identified privacy as a key issue when utilising telehealth, particularly for adolescents. 13 Our third and final theme revealed that connection and communication with clinicians (on both a technical and interpersonal level) was important to respondents.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, one-quarter of physicians surveyed who provided telehealth for SRH issues reported confidentiality concerns. 15 Others have also identified privacy as a key issue when utilising telehealth, particularly for adolescents. 13 Our third and final theme revealed that connection and communication with clinicians (on both a technical and interpersonal level) was important to respondents.…”
Section: Discussionmentioning
confidence: 99%
“… 2022 ; Steiner et al. 2021 ). Some studies, such as ours, found that access to contraception became difficult during lockdowns (Balachandren et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2021 ; Steiner et al. 2021 ). Two of these studies have shown findings that support our findings (Both, Castle, and Hensen 2021 ; Lewis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Research has documented substantial constraints in accessing contraceptive and abortion care early in the pandemic, 4 , 5 , 29 , 30 , 31 , 32 followed by implementation of novel approaches to expand access to care via telehealth, mail order, and pharmacies. 33 , 34 Given that social and economic disruptive events can cause population-level increases in people’s desire to prevent or postpone pregnancy, continued implementation and evaluation of these expanded care models will be important to attain reproductive autonomy during future disruptions.…”
Section: Discussionmentioning
confidence: 99%